Revitalisasi Nilai Budaya Kesenian Kota Pasuruan melalui Eksistensi Sanggar Seni Dharma Budaya - Khamdan Safiudin; Ayu Maya Damayanti (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2022)
The revitalization of the cultural values of the Pasuruan city of arts as an effort and form of the love of Pasuruan artists in preserving and caring for the traditional values or habits of the Pasuruan city community are packaged in the form of creative dance works. because the artist's persistence became a milestone in the birth of the cultural dharma art studio where since then the artist's gait and actions have been increasingly rafts and even burning to continue to manifest the cultural values of art typical of the city of Pasuruan either through dances or local songs which are then accompanied by musical instruments. So that it can indirectly revive or revive the cultural values of regional arts that were previously deserted of interest and concern from the community. However, with the existence of this cultural dharma art studio, it makes it a vehicle for the community to gain knowledge, information, and treats about the uniqueness of the original culture of the city of Pasuruan which is not only for interest but also to be learned and passed on to the next generation.